Social research a practical introduction - Curtis, Bruce; Curtis, Cate. (London SAGE Publications, 2011)
"Original, fresh, and relevant this is a theoretically-informed practical guide to researching social relations. The text provides a mixed methods approach that challenges historical divisions between quantitative and qualitative research. It adopts a multidisciplinary approach to social science research, drawing from areas such as sociology, social psychology, and social anthropology. Explicitly addressing the concerns of emergent researchers it provides both a ?how to? account of social research and an understanding of the main factors that contextualize research by discussing ?why do? social scientists work this way. Throughout the twelve comprehensive chapters procedural (how to) accounts and contextual (why do) issues are usefully applied to major themes and substantive questions. These key themes include research design; the practices of research and emergent researchers: beyond ontology, epistemology and methodology; the impact of technology on research; and putting the research approach in context. A superb teaching text this book will be relished by lecturers seeking an authoritative introduction to social research and by students who want an accessible, enriching text to guide and inspire them."--Publisher?s website.
Introduction -- In-depth interviewing-the interactive base -- Life histories-private and public issues -- Ethnographic research-studying groups in natural settings --Focus groups-studying artificial groups -- Survey research-studying many cases -- Experimental research-in the laboratory and beyond -- Unobtrusive research-studying artefacts and material traces -- Content research-coding and counting -- Secondary research-more than literature reviews -- Semiotic analysis-studying signs and meanings -- Autoethnographic research-writing and reading self.
Includes bibliographical references and index.
Keywords: Social sciences -- Research; Ethnology -- Methodology